Pengaruh Pemahaman Moderasi Beragama Terhadap Karakter Toleransi Siswa Buddha Di SMA Negeri 1 Ampel - Setyawati, Metta; Nyanasuryanadi, Partono; Sukisno, Sukisno (Dharmas Education Journal (DE_Journal), 2025)
Religious diversity in Indonesia necessitates strengthening tolerance to maintain social harmony, particularly among students. This study aims to analyze the influence of understanding religious moderation on the tolerance character of Buddhist students at SMA Negeri 1 Ampel, Boyolali. Employing a descriptive quantitative approach, data were collected from 18 Buddhist students using a validated and reliable structured questionnaire. Simple linear regression analysis revealed a correlation coefficient of 0.766, indicating a strong relationship between religious moderation and tolerance character, with a contribution of 58.6%. These findings confirm that a higher understanding of religious moderation correlates with enhanced tolerance. The study adhered to ethical principles, including obtaining informed consent from respondents. The results provide a foundation for developing character education strategies based on religious moderation, particularly in Buddhist religious education, to foster inclusive attitudes in school settings.